Bioinformatics-based identification of miRNA-, lncRNA-, and mRNA-associated ceRNA networks and potential biomarkers for preeclampsia. Issue 45 (6th November 2020) - Jiang, Ruoan; Wang, Ting; Zhou, Feifei; Yao, Yingsha; He, Jing; Xu, Dong
Abstract : Abstract: This study aimed to identify significantly altered long non-coding RNAs (lncRNAs), microRNAs (miRNAs), mRNAs, pathways in preeclampsia (PE), and to investigate their targeted relationships and biological functions. GSE96985 from Gene Expression Omnibus database was extracted, involving 3 PE and 4 normal tissues. After the differential expression analysis of miRNAs, lncRNAs, and mRNAs using the limma package, protein-protein interaction (PPI) network and module analyses were performed for differentially expressed mRNAs (dif-mRNAs). Combined with the miRanda and miRWalk tools, a regulatory relationship between dif-miRNAs and dif-mRNAs/lncRNAs (dif-mRNAs/dif-lncRNAs) was predicted. Finally, mRNA-miRNA-lncRNA regulatory network construction was performed using Cytoscape software. A total of 511 dif-mRNAs were screened in PE. The top 5 nodes in the PPI networks included up-regulated complement component 3 (C3), C-X-C motif chemokine ligand 8 (CXCL8), and fibronectin 1 (FN1). Three significant network modules were identified for dif-mRNAs. C3 and CXCL8 were identified in module A, and FN1 was identified in module C. A disintegrin and metalloproteinase with thrombospondin motifs 6 (ADAMTS6) was down-regulated by the miR-210-3p. Therefore, lnc-CTD-2383M3.1 functions as a competing endogenous RNA in ADAMTS6 expression regulation by competitively binding to miR-210-3p during the regulation process of PE. C3, CXCL8, FN1, and ADAMTS6 might be involved in the development of PE. The lnc-CTD-2383M3.1-miR-210-3p-ADAMTS6 axis might be a potential regulatory mechanism in PE.